THE APPLICATION OF LEARNING MODEL OF NUMBERED HEAD TOGETHER (NHT) ON THE SUBJECT Course OF THE STARTER SYSTEM OF ELEVENTH GRADE STUDENTS (TKR) OF SMK NEGERI 1 SUKAMARA 2015/2016 ACADEMIC YEAR - Edy Sopyanur; Wiyogo (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
This research aims to know: (1) teacher activity while applying learning of Numbered Head Together on the subject matter of the Starter System, (2) student activity of eleventh grade students (TKR) of SMK NEGERI 1 Sukamara while following application of learning model of Numbered Head Together, (3) students response at eleventh grade students (TKR) of SMK NEGERI 1 Sukamara on learning by using the learning model of Numbered Head Together (NHT) on the subject matter of the starter system, (4) the result of student learning of eleventh grade students (TKR) of SMK NEGERI 1 Sukamara after following learning model of Numbered Head Together (NHT) on the subject matter of the starter system. This research was quantitative descriptive, this research took subject of eleventh grade students (TKR) of SMK NEGERI 1 Sukamara selected as research subject. The instruments used were Cognitive Learning Result Test, Students Activity Sheet, Teacher Activity Sheet and Student Response Questionnaire, and student learning outcomes involving Cognitive and Psychomotor aspects. The results of data analysis indicated that the overall shows that the student activity performed well. The completeness of cognitive learning tests individually there were 26 finished (92%) and 2 unfinished (8%). Classically this learning was said to be completed because the percentage of completeness obtained (92.39%).